Socio-ecological discourse in education for the sustainable development of the North regions; SHS Web of Conferences; Vol. 112 : Northern Sustainable Development Forum 2020 - Egorova G. I. Galina Ivanovna; Niyazova A. Amina; Vartanyan A. Aram; Gibadullina Yu. M. Yuliya Maratovna; Demidova O. M. Olga Mikhailovna (2021, 2021)
Title screen